Employee’s Job Performance: The Effect of Attitude toward Works, Organizational Commitment, and Job Satisfaction - Aries Susanty; Rizqi Miradipta (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2013)
Job satisfaction is a pleasurable or positive emotional state resulting from the appraisal of one’s job and job experiences. The happier the individual, the higher is level of job satisfaction. It is assumed that positive attitude towards work and greater organizational commitment increases job satisfaction which in return enhances performance of the individual. Based on this phenomenon, this study is aimed to explain and empirically test the effect of attitude toward work, job satisfaction, and organizational commitment to the employee’s job performance at PT. Intech Anugrah Indonesia (PT. Intech). Data used in this study was primary data which were collected through closed questionnaires with 1-5 Likert scale. A sample of this study was 200 managerial and non-managerial staff of PT. Intech. Research carried out by using Structural Equation Modeling (SEM) which was run by AMOS 20.0 program. The results of this study showed that attitude towards work have positive but not significant effect to job satisfaction and employee performance. Different with attitude towards work, the organization's commitment has positive and significant effect on job satisfaction and employee performance at PT. Intech. It means every improvement in organization’s commitment has a positive effect toward job satisfaction and employee performance at PT. Intech.